Mesothelial cyst with endometriosis mimicking a Nuck cyst - Uno, Yoshiko (Oxford University Press, 2014)
We report a case of mesothelial cyst protruding from the right femoral ring with suspected endometriosis in a 35-year-old woman, who complained of a lump with a diameter of 6 cm in the right inguinal region. Although she had the hormone therapy during the next 8 months for the diagnosis of extragenital endometriosis, her symptoms did not improve. The clinical suspicion of a Nuck cyst with endometriosis, supported by ultrasonography and magnetic resonance imaging, was confirmed by histopathological examination of the surgical specimen. Authors herein report this unusual case and review the literature.